Nivel de competitividad del Supermercado Jr del cantón Alfredo Baquerizo Moreno (Jujan) periodo 2021. - Muñoz Triviño, Byron Alexander (2022)
The competitiveness of the commercial sector in recent years has grown globally, regionally and locally; In this area, JR Supermarket faces strong competition in its territory, in addition to presenting a weak quality management system oriented to good customer service, from which it is also determined that the staff does not comply with a schedule schedule, also there is irregularity of prices as products of the lack of control in the marking processes, all this has repercussions that it has a not very strong level of competitiveness, therefore the objective of this work is to analyze the level of competitiveness with the purpose of looking for a possible solution. that can be applied knowing that it is a commercial that supplies essential products, from the theoretical framework it was possible to generate arguments and analysis of the conceptualizations proposed, the methods applied in this investigation was the quantitative and qualitative approach, which were of great help to meet the objectives of this work. In the conclusions the proposed and achieved objectives are stated in which it was determined that the economic dynamism today the markets are highly competitive, the establishment under study presents internal and external problems in terms of poor training for work staff, poor advertising and unstable location which affect their competitive level